2020
DOI: 10.20965/ijat.2020.p0769
|View full text |Cite
|
Sign up to set email alerts
|

Patterns for Living Lab Practice: Describing Key Know-How to Promote Service Co-Creation with Users

Abstract: “Value co-creation” among actors related to service provision is one of the key concepts in service design. Living Lab (LL) is a co-creative service design methodology in which designers and users collaboratively design services. In LL, users are actively involved in service design processes over long periods. Because LL is a design methodology based on long-term co-creation with users, its practices involve more direct and indirect communication and collaboration with users than typical service design does. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…According to the European Network of Living Labs (ENoLL), living labs are “open innovation ecosystems in real‐life environments using iterative feedback processes throughout a lifecycle approach of an innovation to create sustainable impact.” 52 This definition shows a clear linkage to the SSV and the aforementioned approaches regarding participation in innovation/design, iterative processes and ecosystems, implying the involvement of multiple stakeholders and real situations/interactions. Indeed, living lab is a “co‐creative service design methodology.” 53 Yasuoka et al 54 . showed it as a cyclical process entailing idea creation, prototyping and user testing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the European Network of Living Labs (ENoLL), living labs are “open innovation ecosystems in real‐life environments using iterative feedback processes throughout a lifecycle approach of an innovation to create sustainable impact.” 52 This definition shows a clear linkage to the SSV and the aforementioned approaches regarding participation in innovation/design, iterative processes and ecosystems, implying the involvement of multiple stakeholders and real situations/interactions. Indeed, living lab is a “co‐creative service design methodology.” 53 Yasuoka et al 54 . showed it as a cyclical process entailing idea creation, prototyping and user testing.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, living lab is a "co-creative service design methodology." 53 Yasuoka et al 54 showed it as a cyclical process entailing idea creation, prototyping and user testing. Akasaka et al 55 further highlighted three features of the living lab method, including "testing in a real-life environment or a similar environment," "involving users from the early to late stages of the process" and a "long-term design process.…”
Section: Living Labsmentioning
confidence: 99%
“…Aiming at transferring tacit knowledge for living lab practice to wider practitioners, the authors conducted a series of experiments, in which practitioners' experiences were collectively extracted and externalized [32], [33](Step 1). The process was conducted through two workshops for collecting tacit knowledge for living lab practice, and an analysis session.…”
Section: Methodsmentioning
confidence: 99%
“…The depicted knowledge was finally externalized in a form of three different representations and evaluated (Step 2). The Step 1, the knowledge extraction process in workshops and analysis were reported previously in a conference [32], [33], so that in this article, only the basic frame and result will be presented.…”
Section: Methodsmentioning
confidence: 99%
“…The programme design comprises one of the features. While initiatives for the use of living labs have started in various places-mostly based on high expectations-there is no clear and unified definition, and, in Japan, in particular, knowledge has not been systematically organised [49]. Additionally, there is a concern that even if a long-term vision is shared, it may not meet short-term expectations because of power issues among stakeholders and the reluctance of end-users, given the wide range of stakeholders [50].…”
Section: Features Of the Case Studymentioning
confidence: 99%